1999
DOI: 10.1136/jnnp.67.6.716
|View full text |Cite
|
Sign up to set email alerts
|

Visual field defects associated with vigabatrin therapy

Abstract: Objective-To estimate the prevalence of visual field defects in patients taking the anticonvulsant drug vigabatrin and to characterise the features of visual dysfunction found. Methods-Thirty three unselected patients attending neurology and epilepsy clinics were identified as taking vigabatrin and asked to attend for neuro-ophthalmic evaluation. A control group of 16 patients with epilepsy unexposed to vigabatrin was also evaluated. Visual fields were examined by static perimetry using a Humphrey field analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
156
2
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(169 citation statements)
references
References 22 publications
7
156
2
4
Order By: Relevance
“…Arndt et al (1999) also found a permanent change in EOG after stopping VGB. Other researchers have claimed that the Arden ratio of the EOG is affected by current use of VGB (Bourcier Bareil et al 1999;Lawden et al 1999;Harding et al 2000;Johnson et al 2000;Coupland et al 2001;GraniewskiWijnands & van der Torren 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Arndt et al (1999) also found a permanent change in EOG after stopping VGB. Other researchers have claimed that the Arden ratio of the EOG is affected by current use of VGB (Bourcier Bareil et al 1999;Lawden et al 1999;Harding et al 2000;Johnson et al 2000;Coupland et al 2001;GraniewskiWijnands & van der Torren 2002).…”
Section: Discussionmentioning
confidence: 99%
“…384 It is not clear whether the retinal pathology is a direct consequence of GABA-transaminase inhibition or is related to some other effect of vigabatrin, such as glutamic acid decarboxylase inhibition. Until it is shown that chronic inhibition of GABA-transaminase sufficient to suppress seizures can be achieved without risk of retinal damage, the utility of GABA-transaminase as an AED target will remain uncertain.…”
Section: Gaba-transaminasementioning
confidence: 99%
“…[5][6][7] The typical visual field loss is unusual in that it is one of the few causes of bilateral nasal field loss with temporal sparing. Screening for field defects with vigabatrin use is essential; however, a high proportion of patients taking this medication are unable to perform reliable field examinations due to their age or associated learning difficulties.…”
Section: Introductionmentioning
confidence: 99%